Elaboration, Thermal and Structural Approach of Manganese Phosphate Glasses Inside the System of K2O-MnO2-P2O5. Issue 1 (March 2020) - Jerroudi, M.; Yousfi, S.; Bih, L.; Bejjit, L.; Haddad, M.; Manoun, B.; Lazor, P.
Abstract: Glasses of the composition (50-x/2) K2 O-xMnO2 -(50-x/2) P2 O5 with (0≤x≤30%mol), have been prepared by standard melt quenching procedures. The amorphous state of the glasses is evidenced using the X-Ray diffraction. Their physical properties were characterized by thermal analysis and density measurements. The density and the glass transition temperature increase with increasing in MnO2 content. To study the structural role of MnO2 oxide in studied glasses, the FTIR and Raman spectroscopies have been employed. It was highlighted that the presence of MnO2 allows the depolymerisation of the phosphate chains and formation of covalent bonds P-O-Mn, which replace P-O-P and P=O linkages.